Ответ:
Объяснение:
1) 1/ 9+10/3-1=22/9=
2)
3)
4) (1-+) *=()*=
5) 4.6*2.5* 10^4*10^-6=11.5*10^-2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
1) 1/ 9+10/3-1=22/9=![2 \frac{4}{9} 2 \frac{4}{9}](https://tex.z-dn.net/?f=2%20%5Cfrac%7B4%7D%7B9%7D)
2)![a^{-5+2+1} =a^{-2} =\frac{1}{a^2} a^{-5+2+1} =a^{-2} =\frac{1}{a^2}](https://tex.z-dn.net/?f=a%5E%7B-5%2B2%2B1%7D%20%3Da%5E%7B-2%7D%20%3D%5Cfrac%7B1%7D%7Ba%5E2%7D)
3)![\frac{2}{m^4} *\frac{m^2}{16} =\frac{1}{8m^2} \frac{2}{m^4} *\frac{m^2}{16} =\frac{1}{8m^2}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7Bm%5E4%7D%20%2A%5Cfrac%7Bm%5E2%7D%7B16%7D%20%3D%5Cfrac%7B1%7D%7B8m%5E2%7D)
4) (1-
+
) *
=(
)*
=![\frac{1}{x^2} \frac{1}{x^2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bx%5E2%7D)
5) 4.6*2.5* 10^4*10^-6=11.5*10^-2